Non-seismic geophysical prospecting model of Beiya gold mine in Western Yunnan Province - Yang, Jian; Wang, Qiao; Liang, Shengxian; Guo, Jing; Muhammad Aqeel Ashraf (Penerbit Universiti Kebangsaan Malaysia, 2017)
According to the basic rules and characteristics of the gold-polymetallic deposits of Beiya gold mine area in terms of mineralization and ore controlling, it is concluded that skarn deposit is the main ore deposit type in this area and the geological conditions are analyzed by the statistics of the physical parameters. Then, the tectonic, rocks, stratum, ore geophysical models have been treated by the forward modeling numerical simulation and the results are analyzed comprehensively. Based on the forward modeling results, combined with the relevant physical differences, the principle and exploration method test and research for the comprehensive geophysical exploration technology has been carried out, covering the induced polarization and magnetic prospecting for the ore body as well as the indirect geophysical exploration method by means of plane gravity data, audio-magnetotelluric sounding for rock mass and tectonics, the mineralization mode-physical forward modeling - geophysical exploration mode has been established and good results have been achieved. Therefore, a location forecast method has been put forward for the concealed skarn type Fe-Au deposit which is adaptive to the mineralized geological background of Beiya and other similar areas.